Islamic financial planning: towards sustaining the financial wellbeing of Muslim families in Malaysia post Covid-19 - Mohd Yusoff, Zarinah; Engku Ali, Engku Rabiah Adawiah; Zakariyah, Habeebullah (İLKE İlim Kültür Eğitim Vakfı, 2021)
Prior to the Covid-19 pandemic, it was reported that over 60% of the people in Malaysia only have enough savings to last them for less than 6 months in the event of loss of income. It is also reported that only 10.8% of urban Malaysian households have enough savings to withstand ‘financial shocks’ resulting from events such as job loss, economic crisis, physical impairment and death. The current Covid-19 pandemic had proven in stronger term that financial preparation is crucial for unpredictable situations such us the financial problems arising from the economic slowdown caused by movement control orders and lockdowns. Many households; especially those whose breadwinners were being laid-off by their companies, or had their salaries cut-off and asked to take unpaid leave – are in difficult financial situation. Only those with minimal debt obligations, steady income stream and enough financial buffer to pay for expenditures for the coming months are not in urgent need of any government assistance. Hence, it is high time to inculcate the knowledge of Islamic financial planning among Muslim families to ensure their wellbeing.